EFEKTIVITAS PENDAPATAN DAERAH KABUPATEN PACITAN DALAM PROSES PEMULIHAN PASCA BENCANA - Devi Nur Cahaya Ningsih (Universitas Halu Oleo, 2020)
Flood and landslide that occurred at the end of 2017 in Pacitan Regency induced huge losses. However, with good cooperation from all levels of The Pacitan's society, the impact of the disasters could resolve in 4 months. This study aims to determine the steps taken by the government of Pacitan Regency to achieve effectiveness in realizing the original regional income of Pacitan Regency, especially for post-disaster recovery. The research method used is descriptive qualitative, through interviews with the Head of the Disaster Management Section of Pacitan Regency. The results obtained indicate The government of Pacitan Regency has policies that can secure their Original Regional Income. The Regional Original Income is always achieved well before disasters, during disasters, and after disasters. Apart from implementing policies, the effectiveness of regional income in the time of disaster recovery process in Pacitan Regency is also encouraged by the assistance funds obtained from the central government, regional governments, and the private sector. Meanwhile, involving the community with an attitude of good cooperation that is one of a characteristic of the Indonesian society could quickly restore the condition of the Pacitan Regency.